Recent advances in the structural biology of the 26S proteasome. (October 2016) - Wehmer, Marc; Sakata, Eri
Abstract: There is growing appreciation for the fundamental role of structural dynamics in the function of macromolecules. In particular, the 26S proteasome, responsible for selective protein degradation in an ATP dependent manner, exhibits dynamic conformational changes that enable substrate processing. Recent cryo-electron microscopy (cryo-EM) work has revealed the conformational dynamics of the 26S proteasome and established the function of the different conformational states. Technological advances such as direct electron detectors and image processing algorithms allowed resolving the structure of the proteasome at atomic resolution. Here we will review those studies and discuss their contribution to our understanding of proteasome function.